Activation of CD4+ and CD8+ T-lymphocytes by insulin and GAD in patients with type 1 or 2 diabetes mellitus - Arneth, Borros; Justus Liebig University Giessen (My University, 2017)
BACKGROUND: The origin of autoimmune disease type 1 diabetes is still unknown.AIM: This study assessed the activation of CD4+ and CD8+ T-lymphocytes by human insulin and human glutamate decarboxylase (GAD) in patients with type 1 or type 2 diabetes mellitus (DM) and healthy volunteers.MATERIALS AND METHODS: The expression of CD69, a marker of T-lymphocyte activity, was determined in whole blood samples by flow cytometry after 12 h of incubation with or without insulin or GAD. The analysis included samples from 12 type 1 DM patients, 14 type 2 DM patients and 12 healthy volunteers.RESULTS: Significant increases in the number of activated CD4+ and CD8+ T-lymphocytes following pre-incubation of whole blood samples with human insulin or GAD were observed in samples from patients with type 1 DM, whereas no activation of these cells was detected in samples from either type 2 DM patients or healthy subjects.DISCUSSION: These results indicated that latent pre-activation of CD4+ and CD8+ T-lymphocytes in response to insulin or GAD epitopes occurred in type 1 DM patients.CONCLUSION: These findings suggest that pre-immunization against insulin and/or GAD might be associated with the development of type 1 DM. Alternatively, these results might reflect a non-specific, bystander autoimmune response.
Keywords: ddc:610